MARINE TOURISM DEVELOPMENT STRATEGY IN RAJA AMPAT - Sela Fofit (Jurnal Scientia, 2023)
Raja Ampat is known as an area that has a unique tour, namely marine tourism. Tourists like Raja Ampat because it presents beautiful nature. The potential for natural beauty that Raja Ampat has is very feasible for development. The development and management of tourism in Raja Ampat is expected to be able to improve the economy of the surrounding community and create a conscious attitude for local residents to continue to protect the Raja Ampat environment. This study uses qualitative research with data collection techniques namely library research. The results of this study are the strategies used for the development of marine tourism in Raja Ampat including 1) Improving access so that tourists can easily travel to tourist attractions; 2) Carry out the collaboration that exists between the community and the government to carry out policies in developing tourism in the Raja Ampat Islands; 3) Maintain and provide facilities that support tourist attractions; and 4) Promoting tourist attractions with the Tourism Village. The aim of forming and enhancing the image of And so that marine tourism development can be carried out in a sustainable manner (sustainable) we can do several things, namely 1) coordinate and cooperate with parties that can provide benefits such as local governments, local communities, mass media and private entrepreneurs; 2) provide all supporting facilities for tourists; and 3) creating appropriate techniques for treating waste by tourists that are environmentally friendly.